Perencanaan Biaya dan Waktu Proyek Pembangunan Rumah Tinggal Tipe 90 m² - Rifaldi Adi Saputra; Era Agita Kabdiyono; Aang Fazri Maulana; Didi Sulaiman; Ananda Eka Prastya; Bagas Apsa Dwi Aryo (Jurnal Multidisiplin Indonesia, 2026)
Construction project planning and control are essential factors in achieving project objectives in terms of time, cost, and quality. This study discusses the planning and control process of a 90 m² residential house construction project. The purpose of this research is to analyze project scheduling, resource allocation, and project control methods to ensure efficient and effective project implementation. The research method used is a descriptive quantitative approach through project scheduling analysis, cost estimation, and monitoring using project management tools such as the Critical Path Method (CPM) and S-curve analysis. The results of the study indicate that proper planning and systematic project control can minimize delays, optimize resource utilization, and maintain project costs according to the budget plan. In addition, regular monitoring during the construction process contributes significantly to improving project performance and reducing potential risks. Therefore, effective project planning and control are crucial in supporting the successful completion of residential construction projects.